Integration and adoption of climate resilient management practices for enhanced productivity of sheep and goats in pastoral communities of northern Kenya - Ojango, Julie M.K.; Gitau, Jennifer; Ndiwa, Nicholas N.; Recha, John W.M.; Gachora, J.; Muigai, A.W.T. (Springer, 2023)
Interventions to improve productivity in pastoral livestock systems of northern Kenya focus on the management of the rangeland resources and grazing areas with few initiatives on changes related to the livestock assets. However, changing climatic conditions with high frequencies of droughts have increased the vulnerability of pastoral communities and necessitate prompt interventions in animal management practices. In 2018, the Ministry of Agriculture, Livestock, Fisheries and Irrigation in collaboration with the International Livestock Research Institute commenced a programme to build the resilience of pastoral holdings using their animal assets rather than depending on humanitarian emergency responses. Interventions necessitated changes in management practices related to sheep and goat production. Core innovation groups (CIG) each comprising 30 pastoral households in select communities were established to model new practices for wider adoption using participatory processes in Isiolo, Marsabit and Turkana Counties. CIG members went through a 3-year phased training programme on animal management practices for more efficient, resilient and productive animals. The adoption of new practices in CIG focks was monitored by extension personnel. Data were analysed using logistic regression techniques to assess household-level adoption of livestock breed improvement, feeding and disease control interventions. The 3 years of the programme (2018–2021) were relatively satisfactory in terms of pasture availability; hence, communities pursued strategies to enhance their focks. All CIG adopted more than one of the introduced technologies concurrently. Prevention of diseases was the most readily adopted, followed by crossbreeding using indigenous breeds of sheep and goats from other arid areas of Kenya. Turkana County had the lowest probability of adopting any of the technologies as previous devastating droughts have resulted in an increased emphasis on animals for survival rather than productivity. The study shows that pastoral communities are open to technological interventions for animal productivity. Adoption of the technologies was enhanced by the experiential capacity development activities adapted to the education level of the different communities